Assessment of microstructural characterization and Thermo-Kinetic simulations for producing strengthened and toughened martensitic steels. (2021) - Harsha, B.P.; Patnaik, Amar; Banerjee, M.K.; Kozeschnik, Ernst
Abstract: Martensitic steels possess higher strength and toughness as the carbon content is minimum and strengthened by precipitation hardening. Hence various factors such as chemical composition, production techniques, heat treatments influencing the properties of martensitic steel were chosen for review. An attempt has been made to understand various available microstructural characterization techniques with their unique features and also predictions as made with the help of thermo-kinetic simulations for microstructure evolution. It is witnessed that vacuum induction melting is preferred for steels to achieve the highest purity. For understanding the evolution of microstructures during heat treatments, studying precipitation kinetics through micrographs has emerged very important for identifying strengthening mechanisms. Professional software can be used for prediction purposes, which also saves a lot of time, effort, and cost. Including Atomic Probe Tomography for microstructural characterization, helps in identifying nano-sized coprecipitation mechanisms.